Bio-based composites for high-performance materials : from strategy to industrial application - Smitthipong, Wirasak, Ed (CRC Press, 2015)
"This timely text integrates disciplines such as materials science, polymer chemistry, plant science, chemical engineering, and nanotechnology to provide comprehensive coverage of the state of the art in bio-based composite materials, as well as their biological feedstocks, basic design principles, properties, industrial applications, environmental friendliness, and life cycles. It presents a strategic and policy-oriented view of bio-based composites, addressing the competing needs for plants as food versus plants as manufacturing feedstocks, while considering the costs of retrofitting existing chemical production plants for bio-based composite manufacture. "--